Immigration experience of Latin American working women in Alicante, Spain: an ethnographic study - Liliana González-Juárez; Ana Lucía Noreña-Peña; Luis Cibanal-Juan (Universidade de São Paulo, 2014)
OBJECTIVE: to describe the experience of Latin American working women regarding immigration, taking into account the expectations and conditions in which this process takes place.METHOD: ethnographic qualitative study. Data collection was performed by means of semi-structured interviews with 24 Latin American immigrant women in Spain. The information collected was triangulated through two focal groups.RESULTS: the expectations of migrant women focus on improving family living conditions. Social support is essential for their settling and to perform daily life activities. They declare they have adapted to the settlement country, although they live with stress. They perceive they have greater sexual freedom and power with their partners but keep greater responsibility in childcare, combining that with the role of working woman.CONCLUSIONS: migrant women play a key role in the survival of households, they build and create new meanings about being a woman, their understanding of life, their social and couple relationships. Such importance is shaped by their expectations and the conditions in which the migration process takes place, as well as their work integration.